The Influence of Tahfidzul Quran Program and Motivation against Student Academic Achievement: A Case Study of PKD and PKP University Students Juanda Bogor - Khoiruddin, Muhammad (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2019)
This study aims to gain an understanding of empirical data on the relationship of Tahfidzul Qur’an Program and Motivation, either individually or together with PKD Student Academic Achievement and PKP University Juanda Bogor. The research hypothesis is that (1) There is a strong and significant influence Tahfidzul Program Student Academic Achievement Qur’an against PKD and PKP University Juanda Bogor (2) There is a strong and significant influence on Academic Achievement Motivation and PKP University Students PKD Juanda Bogor. (3) There is the influence of Tahfidzul Qur’an Program and motivation to learn to academic Student Achievement. In this study, the authors used the survey method with the correlational approach that is implemented in the University Student Juanda Bogor involving PKD and PFM. The data collection is done through observation, interviews, questionnaires, and documentary studies. Data analysis is used correlation analysis with formula product-moment correlation technique. This article concludes that the Tahfidzul Qur’an program contributes positively to student motivation and academic achievement. For this reason, the Tahfidzul Qur’an program is very good to be continued and improved in its implementation.